The tert-amino effect in heterocyclic chemistry: Synthesis of new fused pyrazolinoquinolizine and 1,4-oxazinopyrazoline derivatives - Prajapati, Dipak; Borah, Kalyan Jyoti (Beilstein Journal of Organic Chemistry, 2007)
The synthesis of novel fused heterocycles is based on reactions proceeding by the mechanism of the tert-amino effect, which generalizes cyclization of certain derivatives of 3-methyl-1-phenyl-2-pyrazolin-5-ones. Using this strategy a variety of fused heterocycles is obtained by the Knoevenagel condensation of 5-tert-amino-3-methyl-1-phenylpyrazolone-4-carboxal-dehyde 3 with active methylene compounds such as malononitrile and cyanoacetamide followed by cyclisation using anhydrous zinc chloride.